2016
DOI: 10.1021/acs.langmuir.6b03862
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Viscous Droplets on Superamphiphobic Surfaces

Abstract: The impact of a liquid droplet on a solid surface is one of the most common phenomena in nature and frequently encountered in numerous technological processes. Despite the significant progress on understanding the droplet impact phenomenon over the past century, the impact dynamics, especially the coupling effects between the properties of a liquid and surface wettability on the impact process, is still poorly understood. In this work, we experimentally investigated the impact of viscous droplets on superamphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 60 publications
5
54
0
Order By: Relevance
“…Additionally, we found that the maximum spreading area of glycerin A max−g / A 0−g can also be described by a power law of Amaxg/A0gvβ. For a single‐phase glycerin drop, the exponent β ≈ 0.5 is observed in Figure d, which is consistent with the previous report . However, for the glycerin part of the Janus drop, β < 0.5, and βμh/μl:1491 0.25<βμh/μl:545 0.34<βμh/μl:112 0.4.…”
supporting
confidence: 90%
“…Additionally, we found that the maximum spreading area of glycerin A max−g / A 0−g can also be described by a power law of Amaxg/A0gvβ. For a single‐phase glycerin drop, the exponent β ≈ 0.5 is observed in Figure d, which is consistent with the previous report . However, for the glycerin part of the Janus drop, β < 0.5, and βμh/μl:1491 0.25<βμh/μl:545 0.34<βμh/μl:112 0.4.…”
supporting
confidence: 90%
“…In Figure 10a, there is not much difference between the different models. The model of Zhao et al [21] agrees well with the experimental data for a homogeneous superhydrophobic surface.…”
Section: Of 14supporting
confidence: 72%
“…For distilled water on the silicon surface θ Y = 68 • , the maximum spreading factor can be calculated from the model of Pasandideh-Fard et al [20] and Zhao et al [21]. The resolutions are shown in Table 2.…”
Section: Of 14mentioning
confidence: 99%
See 1 more Smart Citation
“…Droplet evaporation characteristics depend on surface wettability, contact angle hysteresis (CAH), [14] and surface roughness [15]. There are many ways to measure the surface wettability on substrates such as contact angle measurements, microscopic examination, glass slide method and nuclear magnetic resonance.…”
Section: Drying Droplets Phenomenon On the Substratementioning
confidence: 99%